Design Of Portable Lawn Mower Using Rapid Entire Body Assessment (Reba) Method - Hafeze, Kevin Farell; Ekoanindiyo, Firman Ardiansyah (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
To facilitate their activities, humans will create or design tools to help their activities. Design is the process of manifesting initiatives carried out based on supporting basic theories. The process can be carried out through the stages of selecting components, understanding characteristics and physical, then making a conceptual series according to the selected components so that the tool can be made as expected. The process of mowing the grass commonly carried out by the community is using a machine that is shouldered which is a machine that uses fuel oil, for a long time workers will feel fatigue in the back and especially in the shoulders. The method that will beused in this research is REBA (Rapid Entire Body Assesment), the REBA method is a method used to measure and analyse the posture of workers. From the results of the analysis of work positions and through the Nordic Body Map questionnaire with the REBA method that has been assessed, a score is obtained which is used for consideration of work posture improvement. Keywords: Design, Rapid Entire Body Assessment, Ergonomics, Nordic Body Map, Workposture